Subjective well-being, mobile social media and the enjoyment of tourism experience: a broaden-and-build perspective. Issue 10 (3rd October 2021) - Chen, Ye; Lin, Zhibin; Filieri, Raffaele; Liu, Ran
ABSTRACT: Drawing on the broaden-and-build theory of positive emotions, this study treats tourist pre-existing subjective well-being as an antecedent to the use of mobile social media (MSM) for sharing tourism experiences. The study further examines how the sharing influences tourism experience. Data were collected from a sample of 1084 consumers who have experience of using MSM for sharing tourism experiences. The results show that subjective well-being has a positive effect on sharing tourism experience on MSM, which further leads to the enjoyment of the digitalized tourism experience. The study provides important implications for tourism research and practice.